2017
DOI: 10.1021/acs.chemmater.7b03504
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Engineered Cationic Nanocrystals Stable in Biological Buffers and High Ionic Strength Solutions

Abstract: Progress in colloidal synthesis in the last two decades has enabled high-quality semiconductor, plasmonic, and magnetic nanocrystals (NCs). As synthesized, these NCs are usually capped with long-chain apolar ligands. Postsynthetic surface functionalization is required for rendering such NCs colloidally stable in polar media such as water. However, unlike small anionic molecules and polymeric coatings, producing positively charged stable NCs, especially at high ionic strengths, has remained challenging. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 102 publications
1
42
0
Order By: Relevance
“…This measurement thus confirms that the entire ensemble of NPs has acquired negative surface charge. The coexistence of cationic and anionic highly charged large species would lead to their fast aggregation, followed either by precipitation of aggregates or, in some cases, formation of organized halo structures, as reported elsewhere . Negative‐stain EM images (Figures and ) confirmed that the resulting structures consisted of a core NP coated with a uniform, ≈4‐nm‐thick proteinaceous shell, as expected for a single layer of AaLS‐13 pentamers.…”
Section: Figuresupporting
confidence: 72%
See 3 more Smart Citations
“…This measurement thus confirms that the entire ensemble of NPs has acquired negative surface charge. The coexistence of cationic and anionic highly charged large species would lead to their fast aggregation, followed either by precipitation of aggregates or, in some cases, formation of organized halo structures, as reported elsewhere . Negative‐stain EM images (Figures and ) confirmed that the resulting structures consisted of a core NP coated with a uniform, ≈4‐nm‐thick proteinaceous shell, as expected for a single layer of AaLS‐13 pentamers.…”
Section: Figuresupporting
confidence: 72%
“…We recently reported the preparation of cationic gold nanocrystals derivatized with short (1‐ to 2.5‐nm), positively charged organic ligands . For example, (11‐mercaptoundecyl)‐ N , N , N ‐trimethylammonium bromide (TMABr; Figure B) was found to stabilize 22‐nm AuNPs in water.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…To develop the method of synthesis of size‐defined AgNPs stabilized with (11‐mercaptoundecyl)‐N,N,N‐trimethylammonium chloride (TMA) alkanethiol, a CAPP‐based reaction‐discharge system with direct current atmospheric pressure glow discharge (dc‐APGD) generated in contact with a flowing liquid anode (FLA) was used and optimized in the present contribution. TMA allows to obtain stable nanoparticles, as well as noncytotoxic AgNPs with antimicrobial potential . Previously, dc‐APGD or pulse‐modulated radio‐frequency atmospheric pressure glow discharge (pm‐rf‐APGD), operated between the surface of flowing liquid electrodes and pin‐type W electrodes or a gaseous nozzle jet, was used in our group to synthesize Ag or Ag‐Au core‐shell nanostructures.…”
Section: Introductionmentioning
confidence: 99%